Pelatihan Asertivitas Untuk Meningkatkan Harga Diri Korban Bullying Pada Siswa-Siswi SMPS Amir Hamzah - Sri Hartini; Michael -; Jovinna -; Lani Regina; Cynthia -; William Sutanto; Jericho - (Psikologi Prima, 2024)
The purpose of this study was to determine how well assertiveness training works to improve the self-esteem of victims of bullying both before and after the training. Bullying is a common occurrence in adolescence. This study used an experimental pretest-posttest control group design in a quasi-experimental manner. There were 20 samples in this study divided into two groups. Data were collected through interviews, self-esteem measurements, and observations. T-test was used as the data analysis method. Victims of bullying who received assertiveness training reported higher levels of self-esteem. With a significance of 0.000, the experimental group's T-test result was -7.503, while the control group's finding was -0.688, with a significance of 0.509. The results of the data analysis showed that the experimental group, which received the training, had a significantly higher level of self-esteem. Therefore, it can be concluded that assertiveness training helps victims of bullying feel more confident.